COMMUNITY SERVICE APPLICATION OF SPIRITUAL MINDFULNESS COMBINATION WITH SELF-REGULATION IN REDUCING ANXIETY IN PNEUMONIA PATIENTS - Ayatulloh, Daviq; Priyantini, Diah (Universitas Airlangga, 2025)
Pneumonia, a serious respiratory infection, remains a significant global health challenge in the modern era. This disease not only impacts the physical health of patients, but also often triggers deep anxiety and requires intervention. One form of intervention that can be given is a spiritual approach through mindfulness meditation combined with a self-regulation theory approach to provide positive stimuli in reducing anxiety in pneumonia patients. This community service focuses on implementing a spiritual mindfulness intervention approach combined with self-regulation in reducing anxiety in pneumonia patients. This method is implemented through a series of sessions involving: 1) Introduction to the concept of mindfulness and basic techniques; 2) Integration of spiritual elements according to each patient's beliefs; 3) Self-regulation training, including breathing and relaxation techniques; 4) Daily mindfulness practice with guidance; 5) Group discussions to share experiences and support each other. The characteristics of the participants are an average age of 45.6 years and female gender (60%) is more dominant. The average duration of pneumonia is 14.3 days. Before the intervention, the average score of the patient's anxiety level was 24.8 (indicating moderate anxiety). After being given mindfulness activities, participants showed improvements in their anxiety conditions, the average score was 14.2 (indicating a significant decrease). The combination of mindfulness, spiritual approaches, and self-regulation showed very promising results in reducing anxiety levels in pneumonia patients. This holistic approach combines meditation techniques, spiritual practices, and emotion management strategies for patients.